Pengaruh Efektivitas Penggunaan dan Kepercayaan atas Teknologi Sistem Informasi Akuntansi terhadap Kinerja Karyawan di Perusahaan Besi Beton di Jakarta - Selviana Hoki; Adi Rizfal Efriadi (STIE-JIC, 2022)
The application of information system technology has a propensity to help in winning the existing competition among current businesses. Therefore, this study aims to collect empirical evidence of the effect of Effectiveness in Using Accounting Information System (AIS) Technology, and Trust in AIS technology on Employee Performance for the 51 people who were employed by six reinforcement steel companies in Jakarta. Also, the questionnaire used was processed and analyzed using multiple regression techniques, while respondents were selected with purposive sampling. Based on the research findings, effectiveness of using AIS technology is positively related with employee performance by 48.9%, and trust in using AIS technology is positively related with employee performance by 39.5%. It was also concluded that Effectiveness in Using AIS Technology, and Trust in AIS Technology variables simultaneously affect Employee Performance by 61.3%, whereas the remaining 38.7% is influenced by factors other than the variables being studied. For future research, companies manufacturing other objects besides iron and concrete ought to be included for future research.